Microglia extensively survey the developing cortex via the CXCL12/CXCR4 system to help neural progenitors to acquire differentiated properties. (24th August 2018) - Hattori, Yuki; Miyata, Takaki
Abstract: Neocortical development proceeds through the formation of new zones in which neural‐lineage cells are organized based on their differentiation status. Although microglia initially distribute homogeneously throughout the growing cerebral wall, they accumulate in the inner cytogenic zone, the ventricular zone (VZ) and the subventricular zone (SVZ) in the mid‐embryonic stage. However, the roles of these cells remain to be elucidated. In this study, we found that microglia, despite being only a minor population of the cells that constitute the cerebral wall, promote the differentiation of neural progenitor cells by frequently moving throughout the cortex; their migration is mediated by the CXCL12/CXCR4 system. Pulse‐chase experiments confirmed that microglia help Pax6 + stem‐like cells to differentiate into Tbr2 + intermediate progenitors. Further, monitoring of microglia by live imaging showed that administration of AMD3100, an antagonist of CXCR4, dampened microglial movement and decreased microglial surveillance throughout the cortex. In particular, arrest of microglial motion led to a prominent decrease in the abundance of Tbr2 + cells in the SVZ. Based on our findings, we propose that extensive surveillance by microglia contributes to the efficient functioning of these cells, thereby regulating the differentiation of neural stem‐like cells. Abstract : Microglia, the resident immune cells in the central nervous system, are extensively distributed in the embryonic brain. Despite being only a minor population of the cells that constitute the developing cerebral wall, microglia promote the differentiation from neural stem‐like cells into intermediate progenitors by frequently moving throughout the cortex using the CXCL12/CXCR4 system.